Build up Destination Brand from a City become Destination Tourism - Sakti, Intan Widuri; Sumantri, Dadan (Jurnal Mantik, 2024)
Destination branding is a formation process that can be influenced by several elements where in this study, testimonials and city images are designated that represent the city of Bandung. This gives rise to the results of the study that these two independent variables have a significant positive contribution to the formation of Bandung as a city and tourist destination due to the existence of destination brand, which is dominated by positive city image from testimonials that appear through Instagram stories, photo posts, and testimonials in both cases. Furthermore, we hope that this can be implemented in other cities in West Java and throughout Indonesia, with the hope of increasing regional income through the city as a tourist destination.